Kepastian Hukum Penetapan Sertifikasi Halal di Indonesia Ditinjau Dari Undang-Undang Nomor 6 Tahun 2023 Tentang Cipta Kerja - Nur Efendi, Seftia Wahyu; Wahyoeono H, Dipo (Journal Evidence Of Law, 2024)
This research discusses legal certainty in the determination of halal certification in Indonesia in the Job Creation Law. Definition of Halal Certification, Halal certification is a process to obtain a halal certificate by going through several stages of examination to prove that the raw materials, production process, and product halal assurance system at a company are in accordance with established standards. In Law No.6 of 2023 concerning Job Creation also facilitates halal certification with the issuance of self declare, self declare itself is a statement of the halal status of micro and small business products by the business actors themselves. This research uses normative juridical research methods. In this context, the Job Creation Law introduces significant changes in the regulation of Halal Product Guarantee, including cutting the time for the halal certification process and introducing a self-declare mechanism for micro businesses. These changes are expected to accelerate the growth of the halal food industry in Indonesia and improve the competitiveness of halal products in the global market. As such, this research provides an in-depth understanding of the legal framework governing the establishment of halal certification in Indonesia and how it interacts with the legal changes brought about by the Job Creation Law. This research also identifies the importance of maintaining a balance between bureaucratic simplification and the sustainability of the implementation of Halal Product Guarantee in the context of Indonesian society.